Evaluation of community pharmacy workplace wellness: Literature review, environmental scan, and task force recommendations - Dana Borowitz; Shanna Trenaman; Anastasia Shiamptanis (Elsevier, 2024)
Pharmacy professionals report experiencing burnout and stress in the workplace. Concerns exist that burnout and stress in the pharmacy profession are having an impact on patient care and may be affecting the sustainability of the pharmacy profession. In response, pharmacy regulatory authorities worldwide are exploring how to address workplace wellness. Jurisdictions have varied in terms of the approaches taken, which range from surveys of pharmacy professionals, formation of committees or working groups, and legislative changes. The approach taken by the New Brunswick College of Pharmacists (NBCP) consisted of a literature review of the current state of pharmacy workplace wellness, an environmental scan of approaches to wellness taken in other jurisdictions, a workforce planning survey to gain insight into workplace wellness of pharmacy professionals, and the formation of a task force to make recommendations for improving workplace wellness of New Brunswick pharmacy professionals. Outlining the approach taken in New Brunswick, Canada provides insight that may help other pharmacy regulatory authorities who are considering, or in the process of, implementing a pharmacy workplace wellness initiative.